Gut Microbiota Resilience: Definition, Link to Health and Strategies for Intervention - Dogra, Shaillay Kumar; Doré, Joel; Damak, Sami (Frontiers in Microbiology, 2020)
The gut microbiota is a new frontier in health and disease. Not only many diseases are associated with perturbed microbiota, but an increasing number of studies point to a cause-effect relationship. The gut microbiota is an “organ” with frontline exposure to environmental changes and insults. It is therefore legitimate to postulate that maintaining a resilient microbiota may be important for health. Here we review the concept of resilience, what is known about the characteristics of a resilient microbiota, how to assess microbiota resilience experimentally and how to possibly intervene with nutrients and/or biotics to improve it. We finally discuss some open questions and knowledge gaps.